2019
DOI: 10.1177/1569186119849119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telerehabilitation in occupational therapy practice: A systematic review

Abstract: Objective/background This study aimed to review the current evidence on the application of telerehabilitation in occupational therapy practice and its clinical outcomes over the last 10 years. Methods A systematic review was performed on studies published in English in the decade 2008 to 2017, retrieved from seven electronic databases (MEDLINE, Cochrane Library, CINAHL, Web of Science, SAGE, Science Direct and EMBASE). Only articles evaluating the use of telerehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 39 publications
1
69
1
4
Order By: Relevance
“…Logit regression analysis showed a significant association between the group of physical, occupational, and neurodevelopmental therapists and a good perception of telerehabilitation as a feasible method for maintaining therapeutic goals. Although data are based only on clinical observations made during video calls and not by formal assessment of therapeutic goals, these results are in line with previous studies (62)(63)(64)(65)(66). No significant correlations were observed among the level of agreement with the statements and the group of speech therapists and psychologists.…”
Section: Perception Of Rehabilitation Professionalssupporting
confidence: 86%
“…Logit regression analysis showed a significant association between the group of physical, occupational, and neurodevelopmental therapists and a good perception of telerehabilitation as a feasible method for maintaining therapeutic goals. Although data are based only on clinical observations made during video calls and not by formal assessment of therapeutic goals, these results are in line with previous studies (62)(63)(64)(65)(66). No significant correlations were observed among the level of agreement with the statements and the group of speech therapists and psychologists.…”
Section: Perception Of Rehabilitation Professionalssupporting
confidence: 86%
“… Hung and Fong (2019) only evaluated the effectiveness of rehabilitation for occupational therapy delivered via telehealth and did not use patient satisfaction as the main outcome measure. They also did not find sufficient evidence that telehealth was more effective than standard in-person services ( Hung & Fong, 2019 ). Another systematic review on synchronous telehealth for musculoskeletal conditions found that telehealth was an effective service delivery model and found it to be comparable to standard practices ( Cottrell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine used as a multidisciplinary tele-meeting consumes less time and effort for the families and is more effective for Tele-Guide-lined and Structured Continuous Care (TGSCC). It maintains the added value of multiple specialists assembled without jeopardizing the possibility of discussion and re-evaluation based on real time interaction with the patient and family with all healthcare providers, patients, and caregivers being in their protected environment ( 18 , 39 , 40 ). Such tele-contact also obviates the need for the use of personal protective equipment such as gloves and face masks, limits the risk of viral spread, and offers patients a more natural environment without compromising health care personnel and patients' safety ( 21 ).…”
Section: Multidisciplinary Approachmentioning
confidence: 99%